Building mega-science: A systems engineering tool for the Square Kilometre Array - Colegate, Timothy (?, 2009)
The Square Kilometre Array (SKA) will be the largest radio telescope in the world, with an aperture of up to one million square metres, due to be operational by 2022 at a cost estimated at 1.5 billion euros (2007). Designing a flexible instrument such as the SKA is a long-term task and requires a systems approach with inputs from both engineering and science specialists. Cost and performance modelling, and subsequent optimisation, is central to building the radio telescope. Curtin is taking a lead role in this process, and we present here a custom developed systems engineering tool that is being used in the design phase of the SKA. We outline how such a tool is being used to illuminate the performance and cost trade-offs required for this complex mega-science project reliant on emerging technologies to achieve its scientific goals. We also present some simple design decisions resulting from these trade-offs, saving hundreds of millions of euros.